Layered deposition of porous composite electrodes for high-performance solid-state batteries at ambient temperatures - Leung, P.; Tang, L.; Mohd Rusllim, Mohamed; Xu, Q.; Shah, A.A; Wei, L.; Liao, Qiang (Elsevier Ltd, 2025)
In this study, a novel approach for fabricating solid-state lithium batteries (SSLBs) is introduced, employing atomized layered deposition technology to construct porous composite electrodes that enhance battery performances at room temperatures (22–30 °C). Utilizing a polymeric ionic liquid (PIL)-based polymer as both binder and electrolyte, this research marks a significant advancement in SSLB development by combining improved ionic conductivity (>10−4 S cm−1) with substantial mechanical properties, crucial for the proper functioning of solid-state lithium batteries in ambient conditions. The methodology leverages a mixture of solvents in the layered deposition process to create electrodes with unique porous architectures, thereby facilitating electrolyte infiltration and more efficient battery reactions. Central to this process are the three electrode architectures: a conventional electrode with a polyvinylidene fluoride (PVDF) binder, an electrode incorporating a solid-state electrolyte (SSE) composite and notably, a porous SSE composite electrode. These configurations undergo experimental and model evaluations to investigate ion transport mechanisms and the influence of the proposed electrode structures on optimizing battery performance. The porous SSE composite electrode, fabricated via atomized layered deposition, demonstrates exceptional discharge capacities up to ca. 74 mA h g−1 at 1C and 22 °C.